2019
DOI: 10.2106/jbjs.18.00793
|View full text |Cite
|
Sign up to set email alerts
|

New Persistent Opioid Use Following Common Forefoot Procedures for the Treatment of Hallux Valgus

Abstract: Background: Orthopaedic surgeons are the fourth highest on the list of top prescribers of opioid analgesics by specialty and have a direct impact on opioid-related morbidity in the United States. Operative bunion correction is one of the most commonly performed elective foot surgical procedures in this country. We sought to determine the rate of new persistent opioid use following exposure to opioids after surgical treatment of hallux valgus (bunionectomy) and to identify associated risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…35 In a similar study design, the current authors found new persistent opioid use rates ranging from 6.0% to 7.3% following common procedures for surgical correction of hallux valgus. 19…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…35 In a similar study design, the current authors found new persistent opioid use rates ranging from 6.0% to 7.3% following common procedures for surgical correction of hallux valgus. 19…”
Section: Discussionmentioning
confidence: 99%
“…35 In a similar study design, the current authors found new persistent opioid use rates ranging from 6.0% to 7.3% following common procedures for surgical correction of hallux valgus. 19 Stable ankle fractures are most commonly treated nonoperatively, while unstable fracture patterns often represent more severe bony and soft tissue injuries and require operative fixation. 12 In our analysis, we sought to compare how injury severity might affect persistent opioid use by comparing surgical treatment of common unstable fracture patterns with a non-operatively treated stable ankle fracture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations